Legacy of culture heritage building revitalization: place attachment and culture identity - Chan, Suk Ha Grace; Lee, Wing Han Helen; Tang, Binglin Martin; Chen, Ziyi (Frontiers in Psychology, 2024)
Cultural heritage buildings are revitalised to promote culture instead of being neglected or demolished. For locals, the revitalisation of heritage buildings symbolises a commitment to the community and a taste of collective memory . The study attempts to test the effectiveness of heritage cultural building on visitors'post-experience behaviour through cultural identity and place attachment. Cultural activities engagement' and 'knowledge transfer' serves as moderating attributes. Theirmoderating the effects on cultural identity and place attachment are examined respectively. A valid sample size of 348 from four heritage buildings located in Hong Kong: Tai Kwun, Police Married Quarters(PMQ), Mei Ho House and The Mills. A data analysis platform for PLS-SEM is chosen for this study. Results demonstrate that the effectiveness of heritage building revitalisation on visitors' local cultural identity and emotions leading to place attachment. In our study, the effectiveness of heritage building encompasses three elements which includes appearance and components; technology and planning as well as contribution. Knowledge transfer positively moderates the effectiveness of heritage building revitalisation and cultural identity. However, cultural activity engagement negatively moderates place attachment. Findings also exhibit that place attachment in heritage building revitalisation leads to a positive experience extension. For the practical contribution, the study provides insightsto policy makers and planners for historic building design such as appearance and components, technology in facilitating local visitors' local identity.